Melatonin and circadian rhythms in autism: Case report - Zuculo, Gabriela Melloni [UNESP]; Gonçalves, Bruno S.B.; Brittes, Clay; Menna-Barreto, Luiz; Pinato, Luciana [UNESP] (Taylor & Francis, 2017)
Among the most co-occurring conditions in autism spectrum disorders (ASD), there are sleep disorders which may exacerbate associated behavioral disorders and lead to intensification of existing autistic symptoms. Several studies investigating the use of melatonin in the treatment of sleep disorders in ASD have shown comparative efficiency in sleep with little or no side effects. Here we report a case of ASD with non-24-hour rhythm and the effect of melatonin in circadian parameters by actigraphy. Visual analysis of the first 10 days recorded and the periodogram suggest that this patient showed a non-24-hour rhythm. This ASD subject showed before melatonin administration an activity/rest rhythm lower than 24 hours. The results show that melatonin increased approximately 4.7 times the regularity of circadian activity rhythm and resting staying on average between 00:00 and 06:00 and showed positive effects in improving the quality of sleep and behavior. So, the actigraphy showed an ASD subject with a non-24-hour activity/rest rhythm which changed this rhythm to a 24-hour rhythm after melatonin administration. This result reinforces the prospect of therapy with melatonin for synchronization (increased regularity) of endogenous rhythms and improve sleep quality and hence behavior and indicates the actigraphy as a choice tool to characterize several parameters of the activity/rest rhythm of ASD individuals.
Keywords: actigraphy; behavior; Neurodevelopmental disorder; sleep